Evaluation of Inflammatory Status in COVID-19 Patients with Chronic Kidney Disease: A Comparative Analysis Based on Creatinine Clearance Levels - Andreea Banta; Daniela Rosca; Ovidiu Rosca; Iulia Bogdan; Teodor Cerbulescu; Loredana Gabriela Stana; Elena Hogea; Daciana Nistor (Biomedicines)
Background and Objectives: Patients with chronic kidney disease (CKD) are at increased risk of severe COVID-19 outcomes due to their compromised immune systems and chronic inflammatory state. This study aimed to evaluate and compare the inflammatory status of COVID-19 patients with CKD, stratified by creatinine clearance (CrCl) levels: CrCl < 30 mL/min, CrCl 30–60 mL/min, and CrCl > 60 mL/min. Multiple inflammatory scores combining laboratory parameters were assessed, including novel scores and established indices. Methods: In this retrospective cohort study, 223 patients admitted with confirmed COVID-19 were included and divided into three groups based on CrCl levels: CrCl < 30 (n = 41), CrCl 30–60 (n = 78), and CrCl > 60 (n = 104). Laboratory parameters including C-reactive protein (CRP), interleukin-6 (IL-6), neutrophil-to-lymphocyte ratio (NLR), ferritin, platelet count, absolute neutrophil count (ANC), absolute lymphocyte count (ALC), and serum albumin were collected. Multiple inflammatory scores were calculated, including inflammation scores (IS1–IS4), the systemic inflammatory index (SII), the C-reactive protein-to-albumin ratio (CAR), the lymphocyte-to-C-reactive protein ratio (LCR), and the prognostic nutritional index (PNI). Statistical analyses were performed to compare inflammatory scores among groups and assess correlations with clinical outcomes. Results: The CrCl < 30 group exhibited significantly higher levels of inflammatory markers and inflammatory scores compared with the other groups (p < 0.001). Among the additional scores, CAR and SII were significantly elevated in patients with lower CrCl levels, while LCR and PNI were decreased. CAR showed a strong positive correlation with COVID-19 severity (r = 0.65, p < 0.001), and PNI was inversely correlated with mortality (r = −0.58, p < 0.001). Multivariate regression analysis indicated that lower CrCl levels, higher IS3 and CAR, and lower PNI were independent predictors of severe COVID-19 outcomes. Conclusions: CKD patients with lower CrCl levels have an amplified inflammatory response during COVID-19 infection, as evidenced by elevated inflammatory scores. The additional inflammatory scores, particularly CAR and PNI, may serve as valuable tools for risk stratification and management of COVID-19 in CKD patients. Early identification of patients with high CAR and low PNI could improve clinical outcomes through timely therapeutic interventions.